2015
DOI: 10.18632/oncotarget.3109
|View full text |Cite
|
Sign up to set email alerts
|

Association ofFusobacteriumspecies in pancreatic cancer tissues with molecular features and prognosis

Abstract: Recently, bacterial infection causing periodontal disease has attracted considerable attention as a risk factor for pancreatic cancer. Fusobacterium species is an oral bacterial group of the human microbiome. Some evidence suggests that Fusobacterium species promote colorectal cancer development; however, no previous studies have reported the association between Fusobacterium species and pancreatic cancer. Therefore, we examined whether Fusobacterium species exist in pancreatic cancer tissue. Using a database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
272
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(278 citation statements)
references
References 49 publications
(87 reference statements)
2
272
1
3
Order By: Relevance
“…Among proposed mechanisms for dissemination may result from hepatobiliary translocation or hematogenous seeding[44,46]. However, DNA of different Helicobacter species is mutually exclusive by sampled site[44].…”
Section: Resultsmentioning
confidence: 99%
“…Among proposed mechanisms for dissemination may result from hepatobiliary translocation or hematogenous seeding[44,46]. However, DNA of different Helicobacter species is mutually exclusive by sampled site[44].…”
Section: Resultsmentioning
confidence: 99%
“…Species from the phylum Fusobacteria (particularly F. nucleatum ) are commonly observed in the oral cavity of individuals with periodontal disease, and recent mechanistic evidence has linked F. nucleatum to carcinogenesis 32 . Thus, as suggested by epidemiologic links between the oral microbiota and pancreatic cancer development 33,34 , it may be that Fusobacterium contributes to pancreatic cancer pathogenesis in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Mitsuhashi et al (2015), bacteria can reach the pancreas through circulation, and it has been suggested that this occurs through the biliary tract (transductal transmission) (Zambirinis et al, 2014) to act synergistically with other risk factors, such as obesity and smoking, among others, during carcinogenesis.…”
Section: Pancreatic Cancermentioning
confidence: 96%
“…Furthermore, an estimated 93 283 people are expected to die of this disease. Pancreatic cancer is an aggressive malignancy, with a low rate of survival and therapeutic success (Mitsuhashi et al, 2015;Pevsner-Fischer et al, 2016). Therefore, it is important to further understand its pathogenesis and to search for new diagnostic and therapeutic alternatives (Mitsuhashi et al, 2015;Zambirinis et al, 2014).…”
Section: Pancreatic Cancermentioning
confidence: 99%